Child development a practical introduction - Crowley, Kevin (Sage, 2017)
"Focusing on the earliest years (0-8), the new Second Edition of this best-selling textbook continues to provide a comprehensive overview of the research, theory, and current practice in the field of child development"--Provided by publisher.